Alkaloid-rich fraction of Himatanthus lancifolius contains anti-tumor agents against leukemic cells - Melissa Pires de Lima; Luciana Farhat Hilst; Fernanda Vanessa Rechinbach Mattana; Cid Aimbiré de Moraes Santos; Almeriane Maria Weffort-Santos (Brazilian Journal of Pharmaceutical Sciences, 2010)
The effects of the alkaloid-rich fraction of Himatanthus lancifolius (Müll. Arg) Woodson on normal marrow cells and leukemic cell lines were investigated. After 48 h exposure, the proliferation assay showed significant cell growth inhibition for Daudi (0.1-10 µg/mL), K-562 (1-10 µg/mL), and REH cells (10-100 µg/mL), yet was inert for normal marrow cells. A similar inhibition profile was observed in clonogenic assays. This alkaloid-rich fraction, in which uleine is the main compound, showed no signs of toxicity to any cells up to 10 µg/mL. Cell feature analyses after induction of differentiation showed maintenance of the initial phenotype. Flow cytometric expression of Annexin-V and 7-AAD in K-562 and Daudi cells has indicated that the cells were not undergoing apoptosis or necrosis, suggesting cytostatic activity for tumor cells Os efeitos da fração rica em alcalóides indólicos de Himatanthus lancifolius (Müll. Arg) Woodson sobre células normais de medula óssea e linhagens celulares leucêmicas foram investigados. Após 48 horas de exposição, os ensaios de proliferação demonstraram efeitos inibitórios significativos para as linhagens Daudi (0,1-10 µg/mL), K-562 (1-10 µg/mL) e REH (10-100 µg/mL), enquanto mostrou-se inerte sobre células normais de medula óssea. Os perfis de inibição se repetiram nos ensaios clonogênicos. A fração rica em alcalóides, na qual a uleína é a substância majoritária, não demonstrou toxicidade até a dose de 10 µg/mL para nenhuma das células incluídas no estudo. Da mesma forma, não se observou influência dessa fração sobre a diferenciação celular dessas linhagens, mas manutenção de seu estado maturacional inicial. O conjunto de dados descritos associado à baixa co-expressão de anexina-V e 7-AAD sugerem que esta fração exerce atividade citostática para células tumorais.